Associations Between Fluctuations in Daytime Sleepiness and Motor and Non‐Motor Symptoms in Parkinson's Disease - Höglund, Arja (Mov Disord Clin Pract, 2020)
BACKGROUND: Non‐motor fluctuations are a major concern in Parkinson's disease (PD), and they have been categorized into neuropsychiatric, autonomic and sensory fluctuations. However, this categorization does not include sleep and sleep‐related features, and the association between daytime sleepiness and other motor and/or non‐motor fluctuations in PD remains to be elucidated. OBJECTIVE: To investigate the relationship between daytime sleepiness and other non‐motor and motor fluctuations in people with PD. METHODS: A three‐day home diary recording daytime sleepiness, mood, anxiety, and motor symptoms was used along with the Karolinska Sleepiness Scale (KSS) and 6 days of accelerometer (Parkinson's KinetiGraph™; PKG™) registration to detect motor fluctuations among people with a DaTSCAN verified clinical PD diagnosis (32 men; mean PD duration, 8.2 years). Participants were categorized as motor fluctuators or non‐fluctuators according to the UPDRS part IV and/or the presence of motor and non‐motor fluctuations. RESULTS: Fifty‐two people with PD participated. Daytime sleepiness correlated significantly with motor symptoms, mood and anxiety among those classified as motor fluctuators (n = 28). Motor fluctuators showed stronger correlations between the individual mean level of all diary variables (daytime sleepiness, anxiety, mood and motor symptoms) when compared to the non‐fluctuators (n = 24). Stronger positive within‐individual correlations were found among fluctuators in comparison to non‐fluctuators. In general, PKG data did not correlate with diary data. CONCLUSION: Episodes of daytime sleepiness, as reported by home diaries, were associated with other self‐reported non‐motor and motor fluctuations, but were not supported by PKG data.